Primerjava telesnih značilnosti in gibalnih sposobnosti umetnostnih drsalk s splošno osnovnošolsko populacijo - Umek, Pina (Šport (Ljubljana), 2017)
The purpose of the study was to determine in which physical characteristics and motor abilities figure skaters deviate from the national average, and by how much. 30 female figure skaters, aged 15 to 25, from Slovene skating clubs, participated in the study. All of them skated the entire period of primary education. The results of the SLOfit system in the general population were obtained in the Laboratory for the physical and motor development at the Faculty of sport from the database SLOfit - Športnovzgojni karton. All figure skaters answered the questionnaire, from which was explained correlation between their results and success on competitions. The results point to below-average height, average body mass and below-average amount of subcutaneous fatness of figure skaters. They have better results of all tests of motor abilities than an average primary school population. The most positive deviates are in the standing long jump, sit-ups and bend forward on a bench, and at least positive deviates are in the polygon backwards, arm-plate tapping and a bent arm hang. The greatest impact of figure skating shows in sit-ups and bend forward on a bench. Figure skaters, who were physically more efficient, were statistically significant more successful in competitions, but only at the age of 14 and not at the ages of seven and ten.
Keywords: athletes; figure skating; gibalne sposobnosti; motor abilities; osnovna šola; physical characteristics; primary school; SLOfit; SLOfit system; sport; šport; športnice; športnovzgojni karton; telesne značilnost; umetnostno drsanje